The effectiveness of platelet-rich plasma (PRP) injections in restoring range of motion and reducing pain in Muay Thai players with rotator cuff injuries - Yaseen, Ali Mseer (Journal of Physical Education, 2025)
The research aimed to use the method of platelet-rich plasma (PRP) injection as a relatively modern therapeutic approach to improve the range of motion and reduce pain in Muay Thai players suffering from rotator cuff injuries in the shoulder joint. The research sample included (5) Muay Thai players with rotator cuff injuries in the shoulder joint, with an age of (23.43 ±0.64) years, a mass of (87.74 ±8.19) kg, and a height of (181.39 ±4.21) cm. Their injuries were diagnosed by specialized doctors. Platelet-rich plasma injections were administered once, with a prohibition on training and specific use of the injured joint for 3 days post-injection. Training was resumed after 2 weeks with moderate intensity, and they returned to their designated training load as prescribed by the coach after 3 weeks, with close monitoring of pain and their condition. The range of motion of the shoulder joint was measured based on the American Academy of Orthopedic Surgeons (AAOS). Surgeons - AAOS), and measuring the pain level using the visual analog scale (VAS), which consists of 10 points. The measurements were taken before the injection (pre-test) and 6 weeks after it (post-test). To obtain the research results, the statistical package (SPSS) was used. The study results showed that the use of the Platelet-Rich Plasma (PRP) injection method had a significant effect on increasing the range of motion, reducing pain levels, and restoring shoulder joint function for Muay Thai players, with no negative side effects, and the method did not interfere with the training of Muay Thai players.